Using the global dimension to identify shocks with sign restrictions - Alexander Chudik; Michael Fidora (European Central Bank (ECB), 2011)
Identification of structural VARs using sign restrictions has become increasingly popular in the academic literature. This paper (i) argues that identification of shocks can benefit from introducing a global dimension, and (ii) shows that summarising information by the median of the available impulse responses—as commonly done in the literature—has some undesired features that can be avoided by using an alternatively proposed summary measure based on a “scaled median” estimate of the structural impulse response. The paper implements this approach in both a small scale model as originally presented in Uhlig (2005) and a large scale model, introducing the sign restrictions approach to the global VAR (GVAR) literature, that allows to explore the global dimension by adding a large number of sign restrictions. We find that the patterns of impulse responses are qualitatively similar though point estimates tend to be quantitatively much larger in the alternatively proposed approach. In addition, our GVAR application in the context of global oil supply shocks documents that oil supply shocks have a stronger impact on emerging economies' real output as compared to mature economies, a negative impact on real growth in oil-exporting economies as well, and tend to cause an appreciation (depreciation) of oil-exporters' (oil-importers') real exchange rates but also lead to an appreciation of the US dollar. One possible explanation would be the recycling of oil-exporters' increased revenues in US financial markets.
Keywords: C32; E17; F37; F41; F47; 330; Global VAR; Identification of Shocks; oil shocks; sign restrictions; VAR